RETRACTED: Oxidized LDL Causes Endothelial Apoptosis by Inhibiting Mitochondrial Fusion and Mitochondria Autophagy - Zheng, Jia; Lu, Chengzhi (Frontiers in Cell and Developmental Biology, 2020)
Oxidized low-density lipoprotein (ox-LDL)-induced endothelial dysfunction is an initial step towards atherosclerosis development. Mitochondria damage correlates with ox-LDL-induced endothelial injury through an undefined mechanism. We explored the role of optic atrophy 1 (Opa1)-related mitochondrial fusion and mitophagy in ox-LDL-treated endothelial cells, focusing on mitochondrial damage and cell apoptosis. Ox-LDL treatment reduced endothelial cell viability by increasing apoptosis. Endothelial cell proliferation and migration were also impaired by ox-LDL. At the molecular level, mitochondrial dysfunction was induced by ox-LDL, as demonstrated by decreased mitochondrial membrane potential, increased mitochondrial reactive oxygen species production, augmented mitochondrial permeability transition pore openings, and elevated caspase-3/9 activity. Mitophagy and mitochondrial fusion were also impaired by ox-LDL. Opa1 overexpression reversed this effect by increasing endothelial cell viability and decreasing apoptosis. Interestingly, inhibition of mitophagy or mitochondrial fusion through transfection of siRNAs against Atg5 or Mfn2, respectively, abolished the protective effects of Opa1. Our results illustrate the role of Opa1-related mitochondrial fusion and mitophagy in sustaining endothelial cell viability and mitochondrial homeostasis under ox-LDL stress.